On finite solvable groups decomposable into the product of two nilpotent subgroups - Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish a series of results concerning various properties of a finite solvable groupG=AB with nilpotent subgroupsA andB.